FORMULASI BISKUIT BALITA SEBAGAI PANGANDARURATSUMBER ENERGI PROTEIN DAN VITAMIN ADARI TEPUNG UBI UNGU KACANG HIJAU DAN DAUNKELOR - Febiani Riskika (2020)
Purple sweet potato flour can be a substitute for wheat flour in making biscuits as an energy source. Green beans flour is added to increase the protein value of the biscuits. Moringa leaf flour is added to the biscuits to increase the Vitamin A value. The research objective was to determine the formulation of biscuits for toddlers as a source of energy protein and vitamin A of purple sweet potato flour, green beans, and moringa leaves. The study design used a Completely Randomized Design with three treatments and two repetitions in the formulation with a comparison of purple sweet potato flour and wheat flour F1 80:20, F2 70:30, and F3 60:40. The statistical test used was Kruskall Wallis to see the effect of the biscuit formulation on the hedonic test and if there was continued with a significant difference test mann whitney. The selected formulation was determined based on the bayes method namely F3 biscuits which were then chemically analyzed with control biscuits as a comparison. F3 biscuits contain 482.28kcal energy nutrients, 9.35gr protein, 23.11 gr fat, 59.35 gr carbohydrates, 3.75% moisture content and 2.7% ash content, and Vitamin A 513.3 mcg.